2021
DOI: 10.1371/journal.pone.0240990
|View full text |Cite
|
Sign up to set email alerts
|

“It really proves to us that we are still valuable”: Qualitative research to inform a safer conception intervention for men living with HIV in South Africa

Abstract: Objective Many men living with HIV want to have children. Opportunities to reduce periconception HIV transmission include antiretroviral therapy as prevention, pre-exposure prophylaxis, limiting condomless sex to peak fertility, and sperm processing. Whether men have knowledge of or want to adopt these strategies remains unknown. Methods We conducted focus group discussions (FGDs) with men accessing HIV care in South Africa in 2014 to inform a safer conception intervention for men. Eligible men were 25–45 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…While medical male circumcision and ART use for viral suppression were well-known SC methods, most other methods, including PrEP, were known by 40% of participants or less. Other studies in sub-Saharan Africa have similarly found low but varying information levels about SC methods [ 23 , 25 , 79 ]. While PrEP is a powerful SC option for sero-different couples, the low knowledge of PrEP is not surprising.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…While medical male circumcision and ART use for viral suppression were well-known SC methods, most other methods, including PrEP, were known by 40% of participants or less. Other studies in sub-Saharan Africa have similarly found low but varying information levels about SC methods [ 23 , 25 , 79 ]. While PrEP is a powerful SC option for sero-different couples, the low knowledge of PrEP is not surprising.…”
Section: Discussionmentioning
confidence: 95%
“…Our prior qualitative work in Botswana also found apathy about ART use among WLHIV, making SC approaches to compliment ART use even more relevant [ 34 ]. Similarly, a South African study among MLHIV who desired children found that men wanted to avoid using ART as treatment as prevention [ 79 ]. Clients would benefit from having information about a wide range of SC methods since one approach will not work for all couples and providing options supports reproductive choice [ 22 , 66 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations